2004
DOI: 10.1111/j.1469-8137.2004.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal diversity in photosynthetic terrestrial orchids

Abstract: Summary• Specific orchid-fungal associations are known for nonphotosynthetic orchids but fungal diversity in photosynthetic orchids is thought to be quite broad. Specific fungal associations will figure prominently in conservation efforts, while diverse associations may require less attention. We combined culture techniques with ITS and mtLSU sequences and phylogenetic analysis to determine the genetic diversity of mycorrhizal fungi associated with an evergreen, a spring-green, and a winter-green orchid and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
224
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(237 citation statements)
references
References 54 publications
10
224
1
Order By: Relevance
“…Moreover, symbionts of a number of orchids are difficult or impossible to cultivate axenically [9,35,36], as confirmed from the results obtained through the in vitro isolation attempts performed in our work. As a consequence, molecular methods, based on PCR, used to directly identify fungi within O. tridentata roots, have been essential to characterize fungal diversity in this orchid.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, symbionts of a number of orchids are difficult or impossible to cultivate axenically [9,35,36], as confirmed from the results obtained through the in vitro isolation attempts performed in our work. As a consequence, molecular methods, based on PCR, used to directly identify fungi within O. tridentata roots, have been essential to characterize fungal diversity in this orchid.…”
Section: Discussionsupporting
confidence: 81%
“…2 isolated from adult Dactylorhiza lapponica plants (Fig. 3) (Taylor et al 2002), although McCormick et al (2004) found high fungal specificity in three green North American species. Muir (1989) found enhanced germination in species of Dactylorhiza, Orchis and Serapias from several fungal isolates, especially on the early stages of development.…”
Section: The Effect Of the Presence Of A Fungal Symbiont On Germinationmentioning
confidence: 98%
“…Seeds of Liparis lilifolia, for example, will not germinate in the field or laboratory unless an appropriate fungus is present. The same fungus occurs at all life history stages (Whigham et al 2006) and it is very similar genetically across the range of distribution of the orchid (McCormick et al 2004). Beyond the seeding stage, all terrestrial orchids that were examined are mycorrhizal during some part of the growing season (Rasmussen 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Sebacinoid mycobionts were found in wet habitats in roots of Dactylorhiza incarnata. According to McCormick et al (2004), ORMs of the photosynthetic terrestrial Cephalanthera austinae, Goodyera pubescens, Liparis lilifolia, and Tipularia discolor from the eastern and mid-western USA, comprise Sebacina, although details cannot be found in the data presented. Identification and molecular phylogeny of Epulorhiza isolates from tropical orchids comprised both Sebacina and Tulasnella mycobionts (Ma et al 2003).…”
Section: Mycobionts Of Adult Terrestrial Orchidsmentioning
confidence: 99%